Acute Oral Toxicity of Cincalok Oil in Wistar Rats - Siti Nani Nurbaeti; Inarah Fajriaty; Fajar Nugraha; Hadi Kurniawan; Winda Rahmalia; Thamrin Usman; Dwi I. Prayitno (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Cincalok is a West Kalimantan traditional fermented food that has an opportunity to be developed into supplement products as a source of omega 3 and astaxanthin. This study was designed to observe the acute toxicity of Cincalok oil in female rats for its safety profile using AOT 425 program. Cincalok oil for the acute (2000 and 5000 mg/kg) toxicity studies was administered orally according to the OECD guidelines 425. The rat’s body and organs weight were observed then signs of toxicity were assessed. LD50 was being determined at the end of the study. The result showed that a single dose of Cincalok oil at 2000 or 5000 mg/kg had no lethal effect, behavioral change, a significant change in rat’s bodyweights, or any lesion on the rat’s organs. The LD50 of Cincalok oil for oral administration was higher than 5000 mg/kg and categorized as practically non-toxic.Keywords: Acute Toxicity, Cincalok Oil, LD50.